THE INFLUENCE OF JAPANESE LANGUAGE PROFICIENCY ON THE COMPETENCE OF INDONESIAN CAREGIVER SERVICES IN JAPAN - Rismaja Putra (CV. RADJA PUBLIKA, 2025)
Language skills, particularly in the context of professional communication and caregiving terminology, are an important factor determining service effectiveness, response accuracy, and the quality of interactions between caregivers and service recipients. This study used a quantitative approach with a survey method of Indonesian caregivers working in Japan through the Specified Skilled Worker Program (SSW). The Japanese language proficiency variable measured includes four basic skills (listening, speaking, reading, writing), vocabulary mastery (goi) and grammar, and script comprehension (kanji, hiragana, katakana), which are often measured through standard levels such as the Japanese-Language Proficiency Test (JLPT) from the lowest level N5 to N1 or the Japan Foundation Test for Basic Japanese (JFT). Meanwhile, service competency is assessed based on the dimensions of task knowledge, technical care skills, interpersonal communication, and service quality. The results of the study indicate that Japanese language skills have a significant influence on improving the service competency of Indonesian caregivers, especially in the aspects of communication, accuracy in carrying out work procedures, and understanding the needs of service recipients. This study recommends strengthening Japanese language training programs that focus on the caregiving context as an effort to improve the competence of the Indonesian workforce in this sector.